The CONEVAL. The institutionalization of the official concept of poverty in Mexico / El CONEVAL. La institucionalización del concepto oficial de la pobreza en México - Lukasz Czarnecki (Barataria, 2013)
The establishment of the new democratic institutions is an achievement in the democratic process in contemporary Mexico in the last decade. The National Council for Evaluation of the Social Development Policy (CONEVAL) was created by the Social Development Law (LGDS) in 2004. The creation of the new institution is a challenge in the democratic process in contemporary Mexico. However, it is considered that this institution is a synthesis of contradictory forces, where different power groups, different actors, different parties of the right and left, and several academics achieve to have influences. As a result, there appear the controversies regarding the institutionalization and the importance of the CONEVAL in the framework of the federal institutional design.